Medieval castles and castle mounds on the islands south of Fyn: The situation after 50 years' archaeological investigations - Skaarup, Jørgen (Journal of Danish Archaeology, 1995)
Medieval castles and castle mounds on the islands south of Fyn: The situation after 50 years' archaeological investigations